Fostering agriculture-nutrition links: Recommendations for agriculture extension curriculum reforms in India - Babu, Suresh Chandra; Havimo, Terhi; Pehu, Eija (World Bank, 2015)
Malnutrition continues to be a major development challenge in the South Asia Region. Given its size, India hosts the majority of the malnourished. Around 300 million people in India do not have access to a food supply that sufficiently meets their basic energy needs (World Bank 2012. Nutrition at A Glance: India. Washington, DC: World Bank Group). Despite recent economic growth, poverty remains high, and malnutrition is now manifest in all its forms with overweight and obesity increasing alongside persistent undernutrition and micronutrient deficiencies. The progress made between 1970 and 2010 in reducing malnutrition was largely due to improving access to safe water, female education, and female empowerment, the latter 2 especially key in South Asia. The factor that made the least progress between 1995 and 2010 is increasing quantity and quality of food, clearly a responsibility of agriculture (L. Smith and L. Haddad 2014, “Reducing Child Undernutrition: Past Drivers and Priorities for the Post-MDG Era.” IDS Working Paper 441).